Retour de flamme 02 : la fabuleuse enfance du cinéma - Bromberg, Serge; Lange, Eric (Paris : Lobster Films, 2006)
- Those awful hats = ces sacrés chapeaux / D. W. Griffith ; cop. 1909 (2 min) ##- The mystery of the leaping fish = le mystère des poissons sauteurs / John Emerson, réal. ; Tod Brownin, scénario ; cop. 1926 (26 min) ##- La course au singe ; cop. 1919 (4 min) ##- Pour la fête de sa mère ; cop. 1906 (2 min) ##- Kiriki, acrobates japonais ; cop. 1907 (2 min) ##- La marseillaise ; cop. 1907 (2 min) ##- Week-end ; cop. 1938 (2 min) ##- Clo-cloche ; cop. 1935 (2 min) ##- Play safe = Le petit mécano / Max Fleischer ; cop. 1936 (7 min) ##- Baisers volés ; cop. 1920 (2 min) ##- Mode de Paris ; cop. 1926 (5 min) ##- Black and Tan / Dudley Murphy ; cop. 1929 (18 min) ##- 3 films d'animation du dessinateur O'Galop ; cop. 1918 (6 min) ##- Dr Pyckle and Mr Pride / Percy Pembroke ; cop. 1925 (19 min) ##- Porky's preview = L'avant-première de Porky ; cop. 1941 (6 min) ##- Le raid en avion : épisode 2 / Willy Wolf ; cop. 1924 (24 min)
French or English language tracks with optional English or French subtitles.
film
Keywords: ACAD